2010
DOI: 10.1371/journal.pone.0011301
|View full text |Cite
|
Sign up to set email alerts
|

The Terminal Immunoglobulin-Like Repeats of LigA and LigB of Leptospira Enhance Their Binding to Gelatin Binding Domain of Fibronectin and Host Cells

Abstract: Leptospira spp. are pathogenic spirochetes that cause the zoonotic disease leptospirosis. Leptospiral immunoglobulin (Ig)-like protein B (LigB) contributes to the binding of Leptospira to extracellular matrix proteins such as fibronectin, fibrinogen, laminin, elastin, tropoelastin and collagen. A high-affinity Fn-binding region of LigB has been localized to LigBCen2, which contains the partial 11th and full 12th Ig-like repeats (LigBCen2R) and 47 amino acids of the non-repeat region (LigBCen2NR) of LigB. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
2
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 47 publications
(75 reference statements)
1
60
2
8
Order By: Relevance
“…LigA and LigB may aid in the colonization of L. interrogans by binding with high affinity to components of the extracellular matrix (15)(16)(17)(18)(19). The Lig proteins may also facilitate dissemination by interacting with proteins that control hemostasis (19)(20)(21).…”
mentioning
confidence: 99%
“…LigA and LigB may aid in the colonization of L. interrogans by binding with high affinity to components of the extracellular matrix (15)(16)(17)(18)(19). The Lig proteins may also facilitate dissemination by interacting with proteins that control hemostasis (19)(20)(21).…”
mentioning
confidence: 99%
“…The domains have identical N-terminal sequence, but their C termini are variable [10,11]. The importance of the C-terminal repeats of the immunoglobulin-like domains of LigA has been demonstrated, which is enhancing binding affinity to fibronectin [12]. It was reported that Calcium could bind Lig proteins and modulates fibronectin binding [10].…”
Section: Introductionmentioning
confidence: 99%
“…Lig proteins interact with numerous host molecules, notably proteins that mediate attachment to host tissues [22][23][24][25][26][27][28][29]. In this work, we show that these multifunctional leptospiral proteins Figure 7.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, they are upregulated during host infection [16,18,20,46]. These proteins interact with a diverse array of host molecules, including proteins of the extracellular matrix and the coagulation cascade [22][23][24][25][26][27][28][29]. Their functional plurality prompted us to investigate whether they would interact Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation